The Significance Of Morphological Buildings In The Quranic Readings And Their Effect On Determining Meaning - Fadhil Al-Harkani, Mousa Jaafar (Opción, 2019)
Allah the Almighty revealed the writing of the dear to the heart of the Holy Prophet with an Arabic tongue indicated to warn the mother of the villages, and the Arabs were people eloquent and a statement, surprised by the lan- guage and the statement of the Koran, study and analysis, as they considered the best and highest linguistic text invoked linguistically, and rotated Since the Arab tribes had their eloquent and well-known dialects which had a great impact on the complexity of the grammatical and linguistic base, some tribes read the Koran in their dialects, hence some readings appeared by readers seven, nine, ten, or twelve. The number of readings may reach further Very much, what was the only Arab scientists to address these readings, and set them criteria for acceptance and rejection, and was one of these criteria to be approved to draw the Koran or to have a point of language eloquent, and in the light of these standards divided readings into frequent and mono It is known that any change in the building leads to an increase in meaning, that is, the difference in the reading of the wind from the pronunciation of the winds of each of them has significance. By readers, word structures have meanings, These meanings help to clarify the meaning or breadth or sometimes be a reason to reflect the real readings, weights have meanings for Arabs, but the difference of meanings comes to the difference of buildings, and this is what separated by saying Dr. Ibrahim Samarrai in the book meanings of the Arab buildings, any difference in the building leads To the different meaning, it is necessary to know the morphological buildings and their implications and the definition of reading and the most famous readers in the world of read- ings, and I have presented the meanings of morphological buildings in some of the Qur’anic readings that show the impact of morphological buildings in the meaning.